KONSEP MULTIKULTURALISME DALAM MEMBANGUN MASYARAKAT YANG INKLUSIF - Umi Muflichati; Asih Agus Nur Cahya Ningrum; Ahmad Manshur (STKIP Subang, 2026)
Multiculturalism is a concept that explains the cultural diversity that exists within society and the importance of mutual respect for these differences. This article aims to explain the meaning, principles, and importance of multiculturalism in social life. The method used in writing this article is qualitative research with a library research approach. Data and information were obtained from various sources, such as books, journals, and scientific articles related to the concept of multiculturalism. The results of the study indicate that multiculturalism emphasizes tolerance, equality, mutual respect, and acceptance of differences in culture, language, religion, ethnicity, and traditions within society. With an understanding of multiculturalism, it is hoped that society will be able to live in harmony, peace, and cooperation despite their diverse backgrounds. Furthermore, the concept of multiculturalism also plays a crucial role in fostering unity and solidarity amidst existing diversity. Therefore, the application of multicultural values is crucial in social life and education to create a just, harmonious, and respectful society.